HOUSE OWNING CHALLENGES AND SOLUTIONS FOR MALAYSIAN FIRST HOME BUYERS IN THE POSTCOVID- 19 PANDEMIC ERA (Jurnal Pembangunan Sosial, 2022)
This study intended to identify the factors and solutions that help first home buyers successfully purchase their first home after the COVID-19 pandemic where the current issues and challenges faced by first home buyers in Malaysia should be investigated. The housing prices are still pricey and the prices are progressively rising every year, as the economy develops. However, household income has not increased in lockstep, which is the primary cause of Malaysians’ inability to purchase a home. Furthermore, during the COVID-19 pandemic, this scenario intensifies as economic containment tactics have a negative impact on the economy and social aspects. This study adopted a quantitative research method where the primary data were collected through online survey. The survey was conducted through internet platforms such as Facebook, Instagram, and WhatsApp to collect more responses as online survey brings convenience to respondents. 155 feedbacks were collected from the respondents. From the results, the personal income has the highest impact on the affordability of respondents to purchase their first property in Malaysia where the respondents think the government should promote more incentives and initiatives in helping youngsters to purchase their first home. The government should emphasize the housing sector development as this sector is linked with social development significantly in term of citizens’ satisfaction level with the government policies. The outcomes can be referred to by first home buyers when they encounter similar situations as guidance to help them understand the problems. Although, the government has implemented several housing measures, including allocating available homes to qualifying homebuyers but it is insufficient. The outcomes can help the solutions developed by the government and private banking companies in resolving and alleviating the challenges reported by first home buyers in Malaysia.